Phytoplankton response to winter warming modified by large-bodied zooplankton: an experimental microcosm study - Hu He; Xiaolong Zhu; Xiaolan Song; Erik Jeppesen; Zhengwen Liu (Journal of Limnology, 2015)
While several field investigations have demonstrated significant effects of cool season (winter or spring) warming on phytoplankton development, the role played by large-bodied zooplankton grazers for the responses of phytoplankton to winter warming is ambiguous. We conducted an outdoor experiment to compare the effect of winter warming (heating by 3°C) in combination with presence and absence of Daphnia grazing (D. similis) on phytoplankton standing crops and community structure under eutrophic conditions. When Daphnia were absent, warming was associated with significant increases in phytoplankton biomass and cyanobacterial dominance. In contrast, when Daphnia were present, warming effects on phytoplankton dynamics were offset by warming-enhanced grazing, resulting in no significant change in biomass or taxonomic dominance. These results emphasize that large-bodied zooplankton like Daphnia spp. may play an important role in modulating the interactions between climate warming and phytoplankton dynamics in nutrient rich lake ecosystems.